2020
DOI: 10.1101/2020.04.23.20076661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of angiotensin converting enzyme inhibitors and angiotensin receptor blockers on death and severity of disease in patients with coronavirus disease 2019 (COVID-19): A meta-analysis

Abstract: Aims and Methods: Effect of angiotensin converting enzyme inhibitors (ACEi) and angiotensin receptor blockers (ARB) on outcomes in patients with coronavirus disease 2019 (COVID-19) is uncertain. Available evidence is limited to a few retrospective observational studies with small number of patients. We did a meta-analysis to assess the effect of ACEi/ARB in patients with COVID-19 on severity of disease, risk for hospitalisation, and death compared to those not on ACEi/ARB. We searched the Cochrane library, Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 24 publications
(28 reference statements)
3
44
1
1
Order By: Relevance
“…Based on nonhuman animal models, RAAS inhibitors were predicted to increase ACE2 levels thereby elevating COVID-19 morbidity and mortality. 31,54,55 However, our findings in this DKD cohort counter such predictions by providing evidence for an absence of RAAS inhibition-associated ACE2 expression induction in PTECs. Meanwhile, a series of case-control, database, and electronic health record studies also did not find any association of RAAS inhibitors with poor outcomes in 3 independent cohorts of patients with COVID-19 and RAAS exposures.…”
Section: Q11supporting
confidence: 48%
“…Based on nonhuman animal models, RAAS inhibitors were predicted to increase ACE2 levels thereby elevating COVID-19 morbidity and mortality. 31,54,55 However, our findings in this DKD cohort counter such predictions by providing evidence for an absence of RAAS inhibition-associated ACE2 expression induction in PTECs. Meanwhile, a series of case-control, database, and electronic health record studies also did not find any association of RAAS inhibitors with poor outcomes in 3 independent cohorts of patients with COVID-19 and RAAS exposures.…”
Section: Q11supporting
confidence: 48%
“…Interestingly, ACE inhibitors and ARBs were associated with reduced odds for inpatient mortality and a critical or fatal outcome (OR = 0.33, 95% CI 0.22-0.49, I 2 = 0%, and OR = 0.32, 95% CI 0.22-0.46, I 2 = 32%, respectively) [50]. Similarly, Ghosal et al found a significant decrease in the odds for death with the use of ACE inhibitors/ARBs (OR = 0.57, 95% CI 0.37-0.88, I 2 = 0%), while non-significant benefits were also observed in terms of developing severe disease or hospitalization (OR = 0.62, 95% CI 0.31-1.23, I 2 = 70.36%, and OR = 0.81, 95% CI 0.42-1.55, I 2 = 0%, respectively) [51]. Nevertheless, the former meta-analysis included five and the latter six studies, most of which were located in China.…”
Section: Discussionmentioning
confidence: 98%
“…Recent publications further highlight the use of ACE-I and ARBs in providing cardiovascular and renal benefits to patients with COVID-19 diagnosis [59,60]. In a metaanalysis, patients treated with ACE-I/ARBS had 44% reduction in odds of developing severe disease and death compared with patients not treated with ACE-I/ARBs [61]. These studies provide rationale for investigation into the utility of ACE-I/ARBs in the ethnic population with known prevalence of ACE deletion polymorphisms in an effort to mitigate severity and improve outcomes in response to COVID-19 infections.…”
Section: Ace-2 Inhibition By Covid-19: Increased Ras Activitymentioning
confidence: 99%